PENGARUH KUALITAS KEHIDUPAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT TASPEN (PERSERO) KANTOR CABANG UTAMA BANDUNG - Andini Quentinnisa (2021)
This study used quantitive approach to find if there is any influence of quality of work life and workload on employee performance. Object on this study was employee of PT TASPEN (PERSERO) Bandung Main Branch. The data used in the study was collected and distributed by google form to 48 employees. Saturated sampling of 48 employees used as the sampling method on this study. This study used SmartPLS 3.0 as the tool to analyze this study. After analyzing, the results found on this study are: 1) quality of work life has a significant effect on employee performance, 2) workload does not have a significant effect of employee performance.